Dielectric relaxation studies in activated carbon doped Titanium Dioxide at high temperatures (2017)
(Eng) Titanium Dioxide (TiO2) has been an object of different investigations in the recent years, principally to its applications in solar cells due to its interesting optic, electric and magnetic properties. In this work is presented the dielectric response study of activated carbon doped TiO2 in pressed pills in different Molar relations. The electric behavior of the composites is obtained by bringing the samples to a Nitrogen and Helium atmosphere and studying with complex impedance spectroscopy, in the 50Hz to 5 MHz frequency interval and from room temperature to 723 K. The experimental results showed that the Nitrogen atmosphere leads to an anionic doping, in which an nitrogen anion (A) gets into the TiO2 lattice, replacing an oxygen and forming TiO2-x Ax.